Assessment of Integration of Disability Content into Social Work Education. Issue 3 (2nd October 2017) - Ogden, Lydia; McAllister, Carolyn; Neely-Barnes, Susan
ABSTRACT: Three hundred members of the Council on Social Work Education (CSWE) responded to a survey regarding the inclusion of disability content in social work courses and supports needed to increase disability content. Although respondents generally agreed that disability content is important in social work education, its inclusion is inconsistent, with most frequent inclusion in courses on diversity and least frequent inclusion in courses on research. Respondents identified barriers to increasing disability content, including lack of resources for teaching, lack of relevant faculty expertise, and an overcrowded curriculum. Strategies and resources for infusing disability content into social work education are discussed.